Teacher’s Perception on AI Overuse by Students: Did AI Do Your Task? - Wicaksono, Julien Arief; Setiarini, Rimbi Budi; Suharsono, Degita Danur; Surayya, Siti Ayu; Murti, Ghanesya Hari; Sylvia, Sylvia (UIBU, 2025)
Artificial Intelligence (AI) applications such as ChatGPT, Grammarly, and Google Translate are often used by students to help them to find ideas, write, translate, and even organize the ideas. These applications can support learning, yet many teachers have noticed that students are using them excessively. This study aims to look at university English teachers’ perceptions and responses toward students’ overuse of AI tools in asynchronous learning contexts. This study employed a narrative inquiry approach. The source of the data was five narratives from five university teachers reflected on real situations when they suspected students were overusing AI. The narratives were then thematically analysed to identify emerging patterns and emotional responses. The findings of this research highlight some emotional and ethical dilemmas that teachers experienced, the signs they noticed in student work, and the strategies they used to deal with the problems, and he strategies they employed to promote responsible AI use among students. This study also shows that teachers are trying to balance the use of AI as a helpful tool, not a replacement for learning. It also suggests clearer policies from the institutions, better digital ethics education for the students, and stronger support for teachers in today’s AI era.